Canagliflozin reverses Th1/Th2 imbalance and promotes podocyte autophagy in rats with membranous nephropathy - Lv, Xin; Wang, Jian; Zhang, Li; Shao, Xian; Lin, Yao; Liu, Hongyan; Ma, Guangyang; Li, Jing; Zhou, Saijun; Yu, Pei (Frontiers in Immunology, 2022)
Idiopathic membranous nephropathy is the main cause of chronic kidney disease (CKD). Studies have shown sodium–glucose co-transporter 2 (SGLT2) inhibitors significantly delay renal outcomes in patients with CKD, but the exact mechanism remains unknown. In this study, we investigated the mechanism by which the SGLT2 inhibitor canagliflozin attenuates podocyte injury by reversing the imbalance in Helper T cell 1 (Th1) / Helper T cell 2 (Th2) in peripheral blood of rats with membranous nephropathy (MN). MN rats were gavaged with canagliflozin (10 mg/kg/d) and losartan (10 mg/kg/d), respectively, for eight weeks. Compared to the MN group, the urinary ratio of total protein and the creatinine levels of the canagliflozin group decreased significantly. Canagliflozin improved the glomerulus pathological damage, increased the expression levels of podocyte marker proteins. The protective effect of canagliflozin on kidneys was more obvious than that of losartan. Treatment with canagliflozin increased the proportion of Th1 cells by 2.3 times, decreased the proportion of Th2 cells by 68.5%, and significantly restrained the synthesis of immunoglobulin G1 in B-cells and glomerulus subepithelial immune complex deposition. Co-culture of B-cells derived from MN rats with podocytes triggered the activation of phosphorylation of mTOR and ULK1 of podocytes, inhibited podocyte autophagy and resulted in podocyte injury. B-cells derived from canagliflozin treatment rats reversed these effects above. In conclusion, canagliflozin exerts a protective effect on kidneys by reversing the imbalance in Th1/Th2 cells in MN rats and restoring the autophagy of podocytes inhibited by the abnormal immunoglobulin G secretion from B-cells.